(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Seismic activity is a sign of worry as it causes fatal damages to human and also to structures. Structure must exhibit excellent ductility when overloaded during a major earthquake and must be able dissipate large amount of energy to prevent collapse. Moment resisting steel frames are one of the major earthquake resisting system for steel buildings. Major drawback of system is its components get damaged during earthquake and repair work become uneconomical. This problem can avoid by providing replaceable links in beams of moment resisting frames. This study focuses on energy dissipating ability of replaceable links under cyclic loading. Scope of work is to obtain the promising configuration of replaceable links for steel beams. In this paper, nonlinear finite element analysis has been performed on 32 configuration of replaceable links using ANSYS-Workbench to obtain energy dissipating ability of cantilever steel beam with replaceable links. Cantilever steel beam with link has been analysed by keeping beam size constant. Position of the link has been varied to study the performance of link under cyclic loading. Location and dimension of link sections were chosen on the basis of design recommendations for reduced beam section concept. Maximum stress was observed in link portion alone but the portion of beam experiencing very less magnitude of the stress compare to the link portion. Energy dissipation by the beam was increased with increase in value of ‘a/bbeam’ up to a/bbeam=0.7b and it gradually decreased for the values greater than a/bbeam=0.7 for all the variations of ‘S/dlink’.